Biometric parameters and biochemical composition of wild wreckfish (Polyprion americanus). Issue 3 (16th March 2021) - Linares, Fátima; Pérez Rial, Evaristo; Rodriguez, J.L.; Pazos, Gema; Álvarez-Blázquez, Blanca
ABSTRACT: Wreckfish ( Polyprion americanus ) is considered to be a good candidate for European aquaculture. The main biometric parameters were recorded from 86 wild-caught fish (2.6-18 kg of total weight) for 14 months and the gonadosomatic index (GSI), hepatosomatic index (HIS) and viscerosomatic index (VSI) were obtained. Biochemical analyses of muscle, liver and gonads from wild wreckfish showed that wreckfish has a high level of protein in muscle, 84% of dry weight (DW), and low level of lipids (7% DW). Capture season, sex, size or weight of the fish did not have a strong effect on the variability observed in the levels of proteins, lipids and fatty acids of the different tissues. Reared wreckfish have more lipids in mature gonads than wild fish, which may be due to a more lipid-rich diet. However, some polyunsaturated fatty acids (PUFA) such as arachidonic acid (ARA) and docosahexaenoic acid (DHA) reached higher values in wild female gonads than in reared gonads, which could indicate the wreckfish has high requirements in these fatty acids. This study obtained valuable data on the biology and biochemical composition of wreckfish to estimate its nutritional requirements, which could be useful for the future of this species in aquaculture.